Small molecule quercetin binds MALAT1 triplex and modulates its cellular function - Rakheja, Isha; Ansari, Asgar Hussain; Ray, Arjun; Joshi, Dheeraj Chandra; Maiti, Souvi (Molecular Therapy-Nucleic Acids, 2022)
The triple-helix structure at the 30 end of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a long non -cod-ing RNA, has been considered to be a target for modulating the oncogenic functions of MALAT1. This study examines the binding of quercetin-a known triplex binding molecule-to the MALAT1 triplex. By employing UV-visible spectroscopy, circular dichroism spectroscopy, and isothermal titration calo-rimetry, we observed that quercetin binds to the MALAT1 triplex with a stoichiometry of 1:1 and Kd of 495 +/- 61 nM, along with a negative change in free energy, indicating a spontaneous interaction. Employing real-time PCR measurements, we observed around 50% downregulation of MALAT1 transcript levels in MCF7 cells, and fluorescence in situ hybridization (FISH) experiments showed concomitantly reduced levels of MALAT1 in nuclear speckles. This interaction is likely a result of a direct interaction between the molecule and the RNA, as indicated by a transcription-stop experiment. Further, tran-scriptome-wide analysis of alternative splicing changes induced by quercetin revealed modulation of MALAT1 downstream genes. Collectively, our study shows that quercetin strongly binds to the MALAT1 triplex and modulates its functions. It can thus be used as a scaffold for further development of ther-apeutics or as a chemical tool to understand MALAT1 func-tions.